Stability Study of Shield Tunnel Excavation Face Induced by Shield Chamber Pressure Entering in Shallow-Buried Sand Stratum - GE Jun (Chengshi guidao jiaotong yanjiu)
［Objective］ Solve the problem of excavation surface stability during shield tunneling with pressure entry in shallow-buried sandy stratum.To solve the problem of the stability of tunnel face of shield tunnel with pressure into the chamber in shallow buried sandy soil stratum. ［Method］ The limit support pressure during the shield tunneling pressurized chamber entry operation is studied by combining numerical simulation, theoretical analysis and engineering verification methods. Firstly, the active failure phenomenon of shallow-buried sandy soil stratum is studied by numerical simulation, and the corresponding limit support pressure and failure zone shape are obtained. Then, based on the numerical simulation results, the failure mode applicable to shallow-buried sandy soil stratum is constructed, and the corresponding ultimate support pressure is solved. Finally, the model is applied in the Hangzhou Metro Line 5 pressurized inlet project, and the ground settlement is monitored. ［Result & Conclusion］ The limit support pressure increases approximately linearly with the increase of burial depth, and decreases approximately exponentially with the increase of internal friction angle; the instability mode of the shallow-buried stratum presents the shape of lower wedge and upper inverted cone/platform, in which the upper failure zone is further split into the damage core zone and disturbance zone. By comparing with the numerical model and the literature model, it is found that the proposed wedge + inverted cone/platform model can better describe the phenomenon that the damage zone can reach the ground surface due to the inability of the shallow-buried sandy stratum to form an arch; during the shield pressure entry construction of Hangzhou Metro Line 5 project, the maximum ground settlement value caused is 9.5 mm, and the influence range is within 10 m on both sides of the tunnel axis.